North Atlantic MNPS airspace operations manual - International Air Transport Association.; United States. Federal Aviation Administration.; Great Britain. Civil Aviation Authority.; North Atlantic Systems Planning Group. (Washington, D.C. : Federal Aviation Administration, 1980)
Reprint of Sept. 1980 edition published jointly by the Civil Aviation Authority and the International Air Transport Association. Mode of access: Internet.